Endophytic fungal diversity in Theobroma cacao (cacao) and T. grandiflorum (cupuaçu) trees and their potential for growth promotion and biocontrol of black-pod disease - Hanada, Rogério Eiji; Pomella, Alan William Vilela; Costa, Heron Salazar; Bezerra, José Luiz; Loguercio, Leandro Lopes; Pereira, José Odair (Fungal Biology, 2010)
The endophytic niches of plants are a rich source of microbes that can directly and indirectly promote plant protection, growth and development. The diversity of culturable endophytic fungi from stems and branches of Theobroma cacao (cacao) and Theobroma grandiflorum (cupuaçu) trees growing in the Amazon region of Brazil was assessed. The collection of fungal endophytic isolates obtained was applied in field experiments to evaluate their potential as biocontrol agents against Phytophthora palmivora, the causal agent of the black-pod rot disease of cacao, one of the most important pathogens in cocoa-producing regions worldwide. The isolated endophytic fungi from 60 traditional, farmer-planted, healthy cacao and 10 cupuaçu plants were cultured in PDA under conditions inducing sporulation. Isolates were classified based upon the morphological characteristics of their cultures and reproductive structures. Spore suspensions from a total of 103 isolates that could be classified at least up to genus level were tested against P. palmivora in pods attached to cacao trees in the field. Results indicated that ∼70. % of isolates showed biocontrol effects to a certain extent, suggesting that culturable endophytic fungal biodiversity in this system is of a mostly mutualistic type of interaction with the host. Eight isolates from genera Trichoderma (reference isolate), Pestalotiopsis, Curvularia, Tolypocladium and Fusarium showed the highest level of activity against the pathogen, and were further characterized. All demonstrated their endophytic nature by colonizing axenic cacao plantlets, and confirmed their biocontrol activity on attached pods trials by showing significant decrease in disease severity in relation to the positive control. None, however, showed detectable growth-promotion effects. Aspects related to endophytic biodiversity and host-pathogen-endophyte interactions in the environment of this study were discussed on the context of developing sustainable strategies for biological control of black-pod rot of cacao. © 2010 The British Mycological Society.
Keywords: Biocontrol Agent; Cocoa; Endophyte; Fungus; Growth Response; Mutualism; Perennial Plant; Species Diversity; Antibiosis; Biodiversity; Pest Control, Biological; Cacao; Evaluation; Fungus; Genetics; Isolation And Purification; Methodology; Microbiology; Parasitology; Physiology; Phytophthora; Plant Disease; Symbiosis; Tree; Antibiosis; Biodiversity; Cacao; Fungi; Pest Control, Biological; Phytophthora; Plant Diseases; Symbiosis; Trees; Amazonia; Bacteria (microorganisms); Curvularia; Fungi; Fusarium; Pestalotiopsis; Phytophthora; Phytophthora Palmivora; Theobroma Cacao; Theobroma Grandiflorum; Tolypocladium; Trichoderma